2021
DOI: 10.1186/s12935-021-01900-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor mutation burden-related signatures in the prognosis and immune microenvironment of pancreatic ductal adenocarcinoma

Abstract: Background High tumor mutation burden (TMB) has gradually become a sensitive biomarker for predicting the response to immunotherapy in many cancers, including lung, bladder and head and neck cancers. However, whether high TMB predicts the response to immunotherapy and prognosis in pancreatic ductal adenocarcinoma (PDAC) remained obscure. Hence, it is significant to investigate the role of genes related to TMB (TRGs) in PDAC. Methods The transcripto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…In this study, we mined seven DEASs from the perspective of the TIME and constructed a prognostic signature to evaluate the response to immunotherapy and clinical outcomes of PAAD patients. High-risk group patients with unsatisfying outcomes presented higher mutation patterns and may respond positively to immunotherapy, which is consistent with the conclusion reached by Tang et al [ 50 ]. Unexpectedly, our signature revealed that high-risk PAAD patients have lower infiltration levels of CD8 T cells, regulatory T cells, and activated memory CD4 T cells.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we mined seven DEASs from the perspective of the TIME and constructed a prognostic signature to evaluate the response to immunotherapy and clinical outcomes of PAAD patients. High-risk group patients with unsatisfying outcomes presented higher mutation patterns and may respond positively to immunotherapy, which is consistent with the conclusion reached by Tang et al [ 50 ]. Unexpectedly, our signature revealed that high-risk PAAD patients have lower infiltration levels of CD8 T cells, regulatory T cells, and activated memory CD4 T cells.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence suggests that high TMB status is associated with clinical response to immunotherapy in a variety of tumors ( 34 , 35 ). Therefore, we evaluated the distribution of somatic genomic mutations between different NRS-score groups in the TCGA-CORD cohort ( Figures 9A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence is growing that high TMB is a feature associated with response to immunotherapy in a variety of tumors, and high TMB levels lead to an increase in tumor neoantigens, which may trigger the immune system to attack the tumor 40 , 41 . Thus, we assessed the correlation of risk score with TMB in the TCGA-GC cohort.…”
Section: Resultsmentioning
confidence: 99%